Creed III [videorecording (DVD)] - Jordan, Michael B. (Michael Bakari), 1987-; Coogler, Keenan; Baylin, Zach, 1980-; Coogler, Ryan, 1986-; Thompson, Tessa, 1983-; Majors, Jonathan, 1989-; Harris, Wood, 1969-; Davis-Kent, Mila; Munteanu, Florian; Rashad, Phylicia, 1948- (Warner Bros. Entertainment, Inc., 2023)
After dominating the boxing world, Adonis Creed has been thriving in both his career and family life. When a childhood friend and former boxing prodigy, Damian, resurfaces after serving a long sentence in prison, he is eager to prove that he deserves his shot in the ring. The face-off between former friends is more than just a fight. To settle the score, Adonis must put his future on the line to battle Damian a fighter who has nothing to lose.